Polygala pubescens Muhl. (Polygalaceae) as a replacement name for P. senega L. var. rosea Michx - Pastore, José Floriano B.; Mota, Michelle (Phytotaxa, 2018)
Polygala pubescens Muhl., often treated as an invalid name (as nomen nudum), is here considered validly published and the legitimate name for Polygala senega L. var. rosea Michx. Establishment of the validity of P. pubescens Muhl. (1813), a taxonomic synonym of Asemeia grandiflora (Walter) Small, makes P. pubescens Mart. (1815) a taxonomic synonym of P. erioptera DC. (1824), a later homonym. Muhlenberg’s names published in two editions of his Catalogus Plantarum Americae Septentrionalis (1813, 1818) are analyzed and discussed. A lectotype for Polygala pubescens Rottler ex Mart. is here designated.